STUDY OF VISUAL FATIGUE DUE TO EXTENDED GADGET USE DURING THE COVID-19 PANDEMIC - Fea Firdani; Putri Nilam Sari; Azyyati Ridha Alfian (Universitas Airlangga, 2023)
Introduction Since the COVID-19 pandemic in Indonesia, many activities have been carried out online from home. This change in activity causes the frequency of gadget use to increase. Looking constantly at gadgets such as laptops, desktops, and mobile phones can risk visual problems or visual fatigue. Aims: this research is to describe visual fatigue and the factors that affect students due to the increasing use of gadgets. Methods This study is a quantitative study with a cross-sectional approach—collected data from April to June 2021. The sample in this study was 200 people. The variables are visual fatigue, viewing distance, eye breaks, and refractive error. Data were collected using a questionnaire distributed to respondents using google Forms. Data were analyzed by univariate and bivariate with 95% CI (α = 0.05). Result The analysis showed that 87% of students experienced visual fatigue, 76% used gadgets at an unsafe distance, 92% did not rest their eyes, 39.5% had refractive errors. Statistical test results between visual fatigue with viewing distance (p-value = 0.53), eye breaks (p-value = 0.04) and refractive error (p-value = 0.44). There is a relationship between eye breaks and visual fatigue. Based on the results of this study, take eye breaks by applying 20-20-20, namely resting the eyes every 20 minutes by turning the eyes to see objects as far as 20 feet for 20 seconds when using gadgets to reduce the risk of visual fatigue.